2012
DOI: 10.1016/j.jacc.2011.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Dynamics and Mechanical Properties of the Aortic Annulus by 4-Dimensional Computed Tomography

Abstract: The aortic annulus, generally elliptic, assumes a more round shape in systole, thus increasing CSA without substantial change in perimeter. Perimeter changes are negligible in patients with calcified valves, because tissue properties allow very little expansion. Aortic annulus perimeter appears therefore ideally suited for accurate sizing in transcatheter aortic valve implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(54 citation statements)
references
References 17 publications
3
49
0
2
Order By: Relevance
“…13 Our data would suggest that, although perimeter changes less through the cardiac cycle, it is still a dynamic measurement. In addition, the perimeter measurements on current tools are not as reproducible across platforms because of the lack of uniform smoothing of the curve model when measuring the perimeter of the annulus.…”
Section: Rationale Of Which Ct Annular Measurement To Use For Sizingmentioning
confidence: 71%
“…13 Our data would suggest that, although perimeter changes less through the cardiac cycle, it is still a dynamic measurement. In addition, the perimeter measurements on current tools are not as reproducible across platforms because of the lack of uniform smoothing of the curve model when measuring the perimeter of the annulus.…”
Section: Rationale Of Which Ct Annular Measurement To Use For Sizingmentioning
confidence: 71%
“…9,16,17 Hamdan et al 16 reported a relative maximum difference in area and perimeter between systolic and diastolic measurements of 6.2% and 0.56% respectively in 35 patients with calcified aortic valves and aortic stenosis, and 11.2% and 2.2% respectively in 11 normal control subjects. On the basis of their study, the investigators suggest that changes in cross-sectional area are mainly due to annular reshaping and deformation of the annulus plane, in particular by diastolic inward bulging of the aortomitral continuity, and to a far lesser extent due to stretch.…”
Section: Discussionmentioning
confidence: 98%
“…Area measurements are subject to potentially greater error with increasing annular elongation. As the annulus becomes progressively more ovoid, the area reduces disproportionately to the perimeter leading to potential underestimation of annular size (9). After many years’ experience in valve sizing and with careful consideration of the previously mentioned dialogue, it is the practice in our centre to use perimeter-derived measurements for the sizing of the annulus.…”
Section: Aortic Annular Anatomy and Implications For The Imagermentioning
confidence: 99%